Cutting seton for the treatment of cryptoglandular fistula-in-ano: a systematic review and meta-analysis - Khamar, J.; Sachdeva, A.; McKechnie, T.; Lee, Y.; Tessier, L.; Hong, D.; Eskicioglu, C. (Techniques in coloproctology, 2024)
Background The use of cutting seton (CS) for the management of cryptoglandular fistula-in-ano has remained controversial because of reports of fecal incontinence, postoperative pain, and extended healing time. The aim of this review was to provide the first synthesis of studies investigating the use of CS for the treatment of cryptoglandular fistula-in-ano. Methods MEDLINE, Embase, and CENTRAL were searched up to October 2022. Randomized controlled trials and observational studies comparing CS with alternative interventions were included, along with single-arm studies evaluating CS alone. The primary outcome was fistula-in-ano recurrence, and secondary outcomes included incontinence, healing time, proportion with complete healing, and postoperative pain. Inverse variance random-effects meta-analyses were used to pool effect estimates. Results After screening 661 citations, 29 studies were included. Overall, 1513 patients undergoing CS (18.8% female, mean age: 43.1 years) were included. Patients with CS had a 6% (95% CI: 3–12%) risk of recurrence and a 16% (95% CI: 5–38%) risk of incontinence at 6 months. CS patients had an average healing time of 14.6 weeks (95% CI: 10–19 weeks) with 73% (95% CI: 48–89%) of patients achieving complete healing at 6 months postoperatively. There was no difference in recurrence between CS and fistulotomy, advancement flap, two-stage seton fistulotomy, or draining seton. Conclusions Overall, this analysis shows that CS has comparable recurrence and incontinence rates to other modalities. However, this may be at the expense of more postoperative pain and extended healing time. Further comparative studies between CS and other modalities are warranted.